2017
DOI: 10.1016/j.ijscr.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic surgery in the prone position for esophageal cancer in patients with situs inversus totalis: A report of two cases

Abstract: IntroductionSitus inversus totalis (SIT) is a rare congenital condition characterized by a complete transposition of thoracic and abdominal organs. Here, we present two successful cases of left thoracoscopic esophagectomy in the prone position for SIT-associated esophageal cancer.Presentation of caseOur first case was of an 82-year-old man who underwent a left thoracoscopic esophagectomy in the prone position, followed by hand-assisted laparoscopic gastric mobilization. Surgical duration and blood loss were 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…To the best of our knowledge, only 11 cases of esophagectomy for esophageal cancer with SIT have been previously reported globally (Table 1). [2][3][4][5][6][7][8][9][10][11] Along with advances in endoscopic technology, MIE has gradually emerged as an effective alternative to open surgery. 12 MIE mainly consists of total MIE (combined thoracoscopic-laparoscopic esophagectomy) and hybrid MIE (thoracoscopic-assisted esophagectomy or laparoscopicassisted esophagectomy).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, only 11 cases of esophagectomy for esophageal cancer with SIT have been previously reported globally (Table 1). [2][3][4][5][6][7][8][9][10][11] Along with advances in endoscopic technology, MIE has gradually emerged as an effective alternative to open surgery. 12 MIE mainly consists of total MIE (combined thoracoscopic-laparoscopic esophagectomy) and hybrid MIE (thoracoscopic-assisted esophagectomy or laparoscopicassisted esophagectomy).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 11 cases of esophagectomy for esophageal cancer with SIT have been previously reported globally (Table 1). 2–11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshida et al rst reported a patient with SIT underwent simultaneous hand-assisted laparoscopic gastric mobilization and thoracoscopic esophagectomy in 2004 [8]. Later, other case reports followed, with cervical anastomosis used in most of cases [2,[9][10][11]. Intrathoracic anastomosis was reported only once [4].…”
Section: Discussionmentioning
confidence: 99%
“…Prior image training with right–left inverted videos has been reported to be helpful to ensure surgical safety . In our case, the surgeon underwent image training before surgery using horizontally inverted thoracoscopic surgical videos of patients with normal anatomy in order to recognize the mirror image anatomy.…”
Section: Discussionmentioning
confidence: 99%